2007
DOI: 10.1099/jmm.0.47140-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of slime production by coagulase-negative staphylococci and enterotoxigenic characteristics of Staphylococcus aureus strains isolated from various human clinical specimens

Abstract: The present study was designed to determine the slime production of coagulase-negative staphylococci (CoNS) and the enterotoxigenic properties of Staphylococcus aureus strains, and to evaluate the clinical importance of slime-producing CoNS and enterotoxigenic S. aureus strains isolated from various human clinical specimens. For this purpose, a total of 120 Staphylococcus strains were isolated and identified, and further characterized for their slime production and enterotoxigenicity. Of the clinical isolates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“…However only few data are available on CONS infections with methicillin resistance from developing countries. [8] In the present study most of the isolates were from pus followed by blood and urine and it is well correlated with previously published studies [9,10,11,12,13] which had clearly shown that CONS were commonly isolated from pus, urine, blood & indwelling catheters. The most common organism identified in our study was S.epidermidis (65.5%) followed by S Saprophyticus (15%), S haemolyticus (10.83%) which was almost in par with the studies conducted by Singh S et al, [14] Adriana N et al, [ 9] Pal & Ayyageri.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…However only few data are available on CONS infections with methicillin resistance from developing countries. [8] In the present study most of the isolates were from pus followed by blood and urine and it is well correlated with previously published studies [9,10,11,12,13] which had clearly shown that CONS were commonly isolated from pus, urine, blood & indwelling catheters. The most common organism identified in our study was S.epidermidis (65.5%) followed by S Saprophyticus (15%), S haemolyticus (10.83%) which was almost in par with the studies conducted by Singh S et al, [14] Adriana N et al, [ 9] Pal & Ayyageri.…”
Section: Resultssupporting
confidence: 79%
“…In the present study 55.83% were slime producing organisms, S. epidermidis (82.09%) was the most common species in producing slime followed by S haemolyticus (8.96%) S. Sciuri (4.48%) which was almost similar to the results shown by few other authors. 2,11,12 Also Seetha KS et al, [2] & Boynukara B et al, [13] reported in their study that 16.07% of S. saprophyticus was producing slime, but interestingly in our study S. saprophyticus didn't produce the slime. On the other hand, it should also be considered that slime production may be affected by various factors, such as medium composition, the presence of carbohydrate, iron and CO 2 and oxidation.…”
Section: Resultscontrasting
confidence: 42%
See 1 more Smart Citation
“…urealyticus with a selective advantage. Biofilms form a barrier around bacteria, protecting them from antibiotics and phagocytes and thus making the treatment of infections very difficult (4,30). However, given the likely value of biofilm formation in providing a positive selective advantage, the question remains as to why biofilm-negative antibiotic-susceptible S. capitis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…11,14,23,31 -40 In the study by Boynukara et al, 35 the rate of slimepositive CNS was 38.5% from blood samples, 20.5% from tracheal aspirates and 12.8% from urinary samples. Catalanotti et al 39 determined that slime-positive S. epidermidis and S. aureus strains showed more surface hydrophobic characteristics than slimenegative ones.…”
Section: Discussionmentioning
confidence: 99%